Acrosomal ultrastructure of stallion spermatozoa cryopreserved with ethylene glycol using two packaging systems - Alvarenga, Marco Antonio [UNESP]; Landim-Alvarenga, F. C.; Moreira, R. M.; Cesarino, M. M. (Equine Veterinary Journal Ltd, 2000)
The present experiments aimed to examine the substitution of glycerol (G) by ethylene glycol (E) as a cryoprotective agent for stallion spermatozoa. Two different ethylene glycol concentrations (5% and 10%) and also the association of glycerol (2%) and ethylene glycol (3%) (E/G) were studied (Experiment 1). In Experiment 2, two packing systems (0.5 x 4.0 ml) were evaluated using both cryoprotectors. In both experiments, the sperm membrane integrity after freezing was evaluated using transmission electron microscopy. The mean post-thaw motility was 34.25, 36.5, 29.25 and 34.75% for G5%, E5%, E10% and E/G, respectively. It was observed that the percentage of motile spermatozoa was significantly smaller (P<0.05) when semen was processed with E10%. A decrease in the acrosome integrity was observed in frozen thawed spermatozoa from all treated groups. It was observed that 28.0, 22.5, 25.5 and 22.5 % of the sperm cells had a normal acrosome following freezing with G5%, E5%, E10% and E/G, respectively. Undulation of the outer acrosomal membrane, acrosomal swelling and loss of acrosomal content density and homogeneity were the most evident ultrastructural alterations observed. In Experiment 2, the post-thaw motility was higher (P<0.05) for sperm frozen in 0.5 ml straws than in 4.0 mi straws, regardless of the cryoprotector used. The ultrastructural evaluation showed 26.7 and 16.0% of intact acrosomes for sperm frozen in 0.5 ml and 4.0 ml straws, respectively. We concluded that ethylene glycol has similar cryoprotective properties to glycerol and that utilisation of 0.5 ml straws improved the ability of horse sperm cells to withstand damage after the cryopreservation process.
Keywords: horse; cryoprotector; stallion; semen; ethylene glycol; ultrastructure